(untitled) - Kazemi, Gholam A. (Hoboken, N.J., 2006)
Groundwater Age is the first book of its kind that incorporates and synthesizes the state-of-the-art knowledge about the business of groundwater dating - including historical development, principles, applications, various methods, and likely future progress in the concept. It is a well-organized, advanced, clearly written resource for all the professionals, scientists, graduate students, consultants, and water sector managers who deal with groundwater and who seek a comprehensive treatment of the subject of groundwater age
Keywords: Groundwater,Radioactive tracers in hydrogeology,Nước ngầm; Analysis,sự phân tích